PENGARUH WAKTU DAN KONSENTRASI ENZIM SELULASE PADA PROSES HIDROLISIS TANDAN KOSONG KELAPA SAWIT MENJADI GLUKOSA - Panca Nugrahini F.; Hermanto Sitompul; Donny Riza Putra (Analit : Analytical and Environmental Chemistry, 2016)
This research discuss about the influence of time and cellulase enzymes consentrate in hydrolisis process of oil palm empty fruit bunches (EFB) into glucose. The aim of this research is to get the highest concentration of glucose. This research have done by using six variation in enzyme hydrolisis process, there are 100 hours and 0.75% cellulase enzyme, 100 hours and 1% cellulase enzyme, 112 hours and 0.75% cellulase enzyme, 112 hours and 1% cellulase enzyme, 124 hours and 0.75% cellulase enzyme, 124 hours and 1% cellulase enzyme. The result of this research shows that the highest glucose concentration is obtainable in 124 hours and 1% cellulase enzyme, that is 187 mg/L. Hydrolisis time and cellulase enzyme concentration take effect on the amount of glucose contained in oil palm EFB, the longer time and the higher cellulase enzyme concentration in hydrolisis enzyme will result the highest glucose concentration and vice versa.